Developing role of forensics in deterring violence and genocide - Huffine, Edwin (Array, 2007)
Forensic testing, especially forensic DNA testing, has made remarkable advances within thepast decade.No longer is such testing reserved for only a few special cases; it can now be used to identify tens of thousands and to help reveal the source of biological samples on scales and in conditions that would have been unimaginable more than a decade ago.Just as the laboratory capabilities of forensic DNA have evolved, so has it legal-judicial applications and implications.Forensic DNA testing needs no longer be reserved for the application only after the fact–after the violence and killing has taken place.A proactive strategy conducted during or prior to the onset of violence instead of years after the conflict has ended has the potential of interceding against violence and against genocide.In this manner, forensic DNA testing, which has proven to be one of the most effective crime deterrents for crimes committed by individuals in Western nations, can be used to help deter organized and “officially” sanctioned and supported violence and killing.It is possible to foresee the use of forensic DNA testing in both a proactive and preventative role against such violence and, thus, in not only identifying the missing, but in playing an active role to help prevent their deaths